(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents some results about thetension state in samples subject to pure bending fatigue process. Numerical simulation based on finit elementmethod was used. The tension field induced by a verticaldeformation imposed at the sample ends was generatedon an original patented machine. The studies werecarried out on two steels currently used in pressurevessels industry. Experimental data are in good agreementwith the simulated ones.